How does the vaccine approval procedure affect COVID-19 vaccination intentions? - Silvia Angerer; Daniela Glätzle-Rützler; Philipp Lergetporer; Thomas Rittmannsberger (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2022)
Peoples' willingness to vaccinate is critical to combating the COVID-19 pandemic. We devise a representative experiment to study how the design of the vaccine approval procedure affects public attitudes towards vaccination. Compared to an Emergency Use Authorization, choosing the more thorough Accelerated Authorization approval procedure increases vaccination intentions by 13 percentage points. Effects of increased duration of the approval procedure are positive and significant only for Emergency Use Authorization. Treatment effects are homogenous across population subgroups. Increased trust in the vaccine is the key mediator of treatment effects on vaccination intentions.
Keywords: I12; I18; C93; D83; 330; vaccination; COVID-19; approval procedure; experiment